INVESTIGATING THE IMPACT OF SCALE IN DESIGN SESSIONS SUPPORTED BY A SPATIAL AUGMENTED REALITY (SAR) TOOL. (May 2020) - Giunta, L.; Dekoninck, E.; Gopsill, J.
Abstract: Spatial Augmented Reality (SAR) differs from other forms of AR by allowing the projection of digital images onto a model. This allows the AR to be more tangible and for interaction to be more realistic. The scale of the model plays a role in the realism but may be constrained by technical factors. This study attempts to understand the influence scale has on a design session by analysing the concept generation process, the ease of designing and the design behaviour. Understanding how these factors are influenced by the model scale betters the understanding of how SAR can influence design.